Chemical Angioplasty with Nitroglycerin for Vasospasm after Subarachnoid Hemorrhage: Case Series and Review - Gatto, Luana Antunes Maranha; Gallo, Bruno Henrique Dallo; Koppe, Gelson Luis; Demartini, Zeferino, Junior (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction Vasospasm is a common and potentially devastating complication in patients with subarachnoid hemorrhage, causing high morbidity and mortality. There is no effective and consistent way to prevent or treat cerebral vasospasm capable of altering the morbidity and mortality of this complication. Animal and human studies have attempted to show improvement in aneurysmal vasospasm. Some sought their prevention; others, the treatment of already installed vasospasm. Some achieved only angiographic improvement without clinical correlation, others achieved both, but with ephemeral duration or at the expense of very harmful associated effects. Endovascular techniques allow immediate and aggressive treatment of cerebral vasospasm and include methods such as mechanical and chemical angioplasty. These methods have risks and benefits.Objectives To analyze the results of chemical angioplasty using nitroglycerin (GTN). In addition, to perform a comprehensive review and analysis of aneurysmal vasospasm.Methods We describe our series of 77 patients treated for 8 years with angioplasty for vasospasm, either mechanical (with balloon), chemical (with GTN) or both.Results Eleven patients received only balloon; 37 received only GTN; 29 received both. Forty-four patients (70.1%) evolved with delayed cerebral ischemia and 19 died (mortality of 24.7%). Two deaths were causally related to the rupture of the vessel by the balloon. The only predictors of poor outcome were the need for external ventricular drainage in the first hours of admission, and isolated mechanical angioplasty.Conclusions Balloon angioplasty has excellent results, but it is restricted to proximal vessels and is not without complications. Chemical angioplasty using nitroglycerin has reasonable but short-lived results and further research is needed about it. It is restricted to vasospasm angioplasties only in hospitals, like ours, where better and more potent vasodilator agents are not available.
Keywords: intracranial vasospasm; balloon angioplasty; nitroglycerin; aneurysmal subarachnoid hemorrhage; cerebral hemorrhage; vasodilator agents